Editorial 8.2 - Lefoe, Geraldine (Journal of University Teaching and Learning Practice, 2011)
Welcome to the second issue, Volume 8 of the Journal of University Teaching and Learning (JUTLP). We are very pleased to see the way the journal continues to grow and the improvement in the quality of the papers. For this we would like to thank our editorial board and reviewers for their considerable efforts in providing valuable feedback to the contributors. Recently many people farewelled the Australian Learning and Teaching Council at the Opera House in Sydney as they presented the final round of Teaching and Learning awards and citations. Recognition for these outstanding teachers, as well as support through a multi-million dollar grant system, has seen the profile of teaching and learning raised significantly within higher education in Australia and we look forward to seeing further support through the government body who have taken over this role.